The Relationship Between the Level of Knowledge and Maternal Attitudes towards Giving the Covid-19 Vaccine to Children Aged 6-17 Years - Tahir S, ⁠Supirman (Omni Health Journal, 2024)
Background: Covid-19 is a disease caused by a new type of coronavirus (SARSCoV-2) at the end of 2019, in December, this outbreak was first detected in Wuhan, Hubei Province, China.The government has made various intervention efforts to overcome the Covid-19 Pandemic intervention efforts are carried out not only through the implementation of health protocols but also other interventions, namely vaccination. Based on the Indonesian Ministry of Health, the type of vaccine given to children aged 12-17 years is sinovac with a dose of 0.5 ml then the Pfizer-BioNTech type of COVID-19 vaccine is also available for everyone aged 12 years and over. Objective: This study aims to determine whether there is a relationship between knowledge and maternal attitudes towards administering the COVID-19 vaccine to children aged 6-17 years in the working area of the health center in Enrekang city, Ranga village. Methods: The research design used was Cross Sectional using cross-tabulation and frequency tests. This research was conducted July-August 2022 in Ranga village consisting of 19 respondents Results: The results of the analysis obtained ρ = 0.000 where the value of ρ is smaller than the value of α = 0.05 which means there is a relationship between knowledge and maternal attitudes towards giving the covid-19 vaccine to children aged 6-17 years in the working area of the health center in Enrekang city, Ranga village. Conclusion: Mother's knowledge and attitude are related to the status of the COVID-19 vaccine in children.